2022
DOI: 10.1002/adhm.202201989
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as Potential Functional Nanomaterials for Tissue Engineering

Abstract: Exosomes are cell‐derived extracellular vesicles of 40–160 nm diameter, which carry numerous biomolecules and transmit information between cells. They are used as functional nanomaterials with great potential in biomedical areas, such as active agents and delivery systems for advanced drug delivery and disease therapy. In recent years, potential applications of exosomes in tissue engineering have attracted significant attention, and some critical progress has been made. This review gives a complete picture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 182 publications
(269 reference statements)
0
23
0
Order By: Relevance
“…The abundant membrane CXCR4 conferred the EC‐targeting ability of these NVs and the endothelial homology promoted the accumulation in ECs. [ 24 ] In this study, we further explored the EC‐targeting effects of exosome mimetics of iPS‐EC NV and DA@iPS‐EC NV. The membrane of iPS‐EC NV was labeled with DiD (red).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abundant membrane CXCR4 conferred the EC‐targeting ability of these NVs and the endothelial homology promoted the accumulation in ECs. [ 24 ] In this study, we further explored the EC‐targeting effects of exosome mimetics of iPS‐EC NV and DA@iPS‐EC NV. The membrane of iPS‐EC NV was labeled with DiD (red).…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] The difficult purification, low yield, and high cost have blocked the biomedical applications of exosomes or extracellular vesicles. [ 24–26 ] Owing to the current limitations of exosome production, some studies have introduced an extrusion approach to preparing nanovesicles (NVs) as mimetics for exosomes. [ 23,27 ] For example, Cui et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows that exosomes with a nanostructure similar to liposomes are also composed of lipid bilayers. They are extracellular vesicles (EVs) secreted by various types of natural cells and are found in physiological fluids such as plasma, interstitial fluid, and saliva [125]. Exosomes in humans transport loaded contents from host to recipient cells, enabling information exchange between them (Figure 6c).…”
Section: Liposomes and Exosomesmentioning
confidence: 99%
“…Recently, the exosomes have been widely investigated for bone tissues regeneration, which could act as the carriers of various genes or drugs and alsoregulate the bone formation process themselves. (Guo et al, 2021a;Bei et al, 2021;Chang et al, 2022;Yao et al, 2022) Exosomes are identified as the nanovesicles which could be constitutively released by plasma membrane fusion, with the responsibility of mediating local and systemic cell-to-cell interaction by transferring the mRNAs, miRNAs, or proteins. (Kalluri and LeBleu, 2020;Kimiz-Gebologlu and Oncel, 2022) Exosomes, with the nanostructures ranging from 50 nm to 200 nm, are an emerging promising therapeutic nanomaterials in biomedical fields, such as targeted drug delivery, clinical diagnosis, and immune regulation.…”
Section: Introductionmentioning
confidence: 99%